(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
Today Kazakhstan applies all existing tools in the world to support innovation. This article analyzes the current state of state regulation of innovative activity in Almaty. In this connection it revealed that innovation play a big role; innovative activity in the country is not a source of increasing the degree of competitiveness in the world market. Providing state support of innovative business growth potential of the innovation sphere in Almaty is very high, taking into account the competitive advantages of the city in the national economic system – the large number of qualified personnel, a developed infrastructure, implemented by government support measures, favorable location and investment climate. Apply belowmentioned benefits important for our country, as, according to our survey, it is the problem of tax brakes factor in taking the initiative in this regard.